Media management Culture and Methods in The Process of Digitalization (National and Foreign Experience) - Ergasheva Nargiza Kaziboy qizi (Zien Journals, 2021)
In this article we will gain an understanding of the process of digitalization of mediamanagement theory and the importance of foreign experience in the development of media management, the experience of the United Kingdom and Russia.
Keywords: Media; internet; United States media; British press